A Single‐Site Platinum CO Oxidation Catalyst in Zeolite KLTL: Microscopic and Spectroscopic Determination of the Locations of the Platinum Atoms1. (1st July 2014) - Kistler, Joseph D.; Chotigkrai, Nutchapon; Xu, Pinghong; Enderle, Bryan; Praserthdam, Piyasan; Chen, Cong‐Yan; Browning, Nigel D.; Gates, Bruce C.
Abstract A stable site‐isolated mononuclear platinum catalyst with a well‐defined structure is presented. Platinum complexes supported in zeolite KLTL were synthesized from [Pt(NH3)4](NO3)2, oxidized at 633 K, and used to catalyze CO oxidation. IR and X‐ray absorption spectra and electron micrographs determine the structures and locations of the platinum complexes in the zeolite pores, demonstrate the platinum‐support bonding, and show that the platinum remained site isolated after oxidation and catalysis.